STUDI LITERATUR PERAN TRADISI BUDAYA DALAM MENJAGA HARMONI SOSIAL MASYARAKAT MULTIKULTURAL DI KARIMUNJAWA - Avatar, Avatar Amer Azzikra; Wahyu Wardhani, Novia (Penerbit Lafadz Jaya, 2026)
This study examines the role of local cultural traditions in maintaining social harmony within the multicultural society of Karimunjawa. Using a qualitative descriptive approach through a literature review method, this study analyzes various scientific sources including journals, books, and previous research. The analysis was conducted through systematic data reduction, categorization, and interpretation to identify patterns and key findings related to social dynamics in Karimunjawa. The findings reveal that social harmony is sustained through intensive social interactions, strong values of mutual cooperation, and the continuity of inclusive local traditions. These traditions function as mechanisms of social integration that strengthen solidarity across diverse ethnic and cultural groups. This study highlights that well-preserved cultural values play a strategic role in managing diversity and preventing social conflict. The findings imply that local traditions can serve as a model for sustainable multicultural harmony in other regions.